Electrocatalytic oxygen reduction to hydrogen peroxide through a biomass-derived nitrogen and oxygen self-doped porous carbon metal-free catalyst. Issue 44 (5th November 2021) - Xin, Shuaishuai; Li, Yifan; Guan, Jing; Ma, Bingrui; Zhang, Chunlei; Ma, Xiaoming; Liu, Wenjie; Xin, Yanjun; Gao, Mengchun
Abstract : The electrocatalytic oxygen reduction reaction (ORR) to hydrogen peroxide (H2 O2 ) by a two-electron pathway is regarded as a green and substitute technique to the anthraquinone method. Abstract : The electrocatalytic oxygen reduction reaction (ORR) to hydrogen peroxide (H2 O2 ) by a two-electron pathway is regarded as a green and substitute technique to the anthraquinone method. However, an important challenge in H2 O2 electrogeneration is to design selective and economic electrocatalysts. Herein, nitrogen and oxygen self-doped porous carbon (NO/PC) was prepared using low-cost alfalfa as a raw material without nitrogen sources and strong oxidants. NO/PC prepared at 500 °C (NO/PC-500) showed the highest H2 O2 selectivity of 85.1%. The H2 O2 electrogeneration performance and stability of a composite gas diffusion electrode with NO/PC-500 as an electrocatalyst were significantly improved at high current density by introducing a polytetrafluoroethylene (PTFE) hydrophobic layer. A NO/PC-500 (g) to PTFE binder (mL) ratio of 1 : 3 was selected as an optimal value to fabricate the composite gas diffusion electrode. X-ray photoelectron spectroscopy combined with density functional theory calculations demonstrated that the OOH adsorption energy on most N/O functional groups (graphitic N, the co-doping of graphitic N and C–O–C, and the co-doping of pyrrolic N and C–O–C) in NO/PC was lower than the H2 O2 adsorption energy, which promoted the two-electron ORR and reduced H2 O2 decomposition. However, the co-doping of pyridine N and C–O–C in NO/PC is not conducive to H2 O2 electrogeneration due to the lowest OOH adsorption energy and the highest H2 O2 adsorption energy. Overall, these results have offered insights into the potential application of biomass-derived heteroatom-doped porous carbon as an effective electrocatalyst for H2 O2 generation.